From transnational voluntary standards to local practices. A case study of forest certification in Russia - Olga Malets (Max Planck Institute for the Study of Societies, 2011)
In this paper, I discuss how local actors translate transnational voluntary standards of responsible natural resource management into on-the-ground practices in domestic settings. Building on an extensive study of forest certification in Russia, I argue that implementation is not a straightforward execution of transnational rules imposed by powerful transnational actors - e.g., international NGOs, multinationals, governments or consumers. Rather, local actors negotiate the ways in which transnational standards are implemented locally in both formal and informal settings, and thereby settle political conflicts over natural resource management and construct new knowledge related to standard implementation and good natural resource management. They use both global ideas reflected in transnational standards and locally available concepts and practices as building blocks, and combine them in various ways in order to construct new knowledge. I therefore emphasize stakeholder interest negotiation and collective learning as core social processes which enable the translation of transnational standards into on-the-ground practices. – – Das Papier beschäftigt sich mit der Frage, wie lokale Akteure freiwillige transnationale Standards für verantwortliches Ressourcenmanagement unter lokalen Rahmenbedingungen umsetzen. Auf der Grundlage einer umfangreichen Untersuchung der Waldzertifizierungspraxis in Russland wird argumentiert, dass die Einführung der Standards nicht über die direkte Implementierung transnationaler und durch einflussreiche transnationale Akteure (internationale Nichtregierungsorganisationen, multinationale Konzerne, Regierungen oder Konsumenten) erfolgt. Wie transnationale Standards vor Ort implementiert werden, verhandeln lokale Akteure in formalen und informellen Foren. Sie lösen politische Konflikte im Bereich des Managements natürlicher Ressourcen und bauen neues Wissen über die Implementierung der Standards und ein gutes Ressourcenmanagement auf. Als Bausteine nutzen sie dabei die in transnationalen Standards reflektierten globalen Grundgedanken sowie vor Ort verfügbare Konzepte und Praktiken und kombinieren diese auf verschiedene Weise. Die Verhandlung von Stakeholder-Interessen und kollektives Lernen sind somit zentrale soziale Prozesse bei der Übertragung transnationaler Standards in die Praxis vor Ort.
Keywords: 300